The influence of perceived ease of use, perceived usefulness, and perceived risk on intention to use Gopay on Gojek application users - Vellya Shafira; Yasri Yasri (Universitas Negeri Padang, 2021)
This study aims to analyze (1) the effect of perceived ease of use on the intention to use Gopay on Gojek application users in the city of Padang. (2) The effect of perceived usefulness on the intention to use Gopay on Gojek application users in Padang City. (3) The effect of perceived risk on the intention to use Gopay on Gojek application users in Padang City. The population in this research is all Gopay users in the city of Padang and the sample in this study were Gopay users on the Gojek application. The research sample was 210 respondents. Data was collected through the distribution of online questionnaires and data processing was carried out through SmartPLS software. The results of this study include: (1) perceived ease of use has a positive effect on the intention to use Gopay on Gojek application users. (2) perceived usefulness has a positive effect on the intention to use Gopay on Gojek application users. (3) perceived risk has a positive effect on the intention to use Gopay on Gojek application users.